Impact of a Fast-track Esophagectomy Protocol on Esophageal Cancer Patient Outcomes and Hospital Charges. Issue 6 (June 2015) - Shewale, Jitesh B.; Correa, Arlene M.; Baker, Carla M.; Villafane-Ferriol, Nicole; Hofstetter, Wayne L.; Jordan, Victoria S.; Kehlet, Henrik; Lewis, Katie M.; Mehran, Reza J.; Summers, Barbara L.; Schaub, Diane; Wilks, Sonia A.; et al.
Abstract : Objective: To evaluate the effects of a fast-track esophagectomy protocol (FTEP) on esophageal cancer patients' safety, length of hospital stay (LOS), and hospital charges. Background: FTEP involved transferring patients to the telemetry unit instead of the surgical intensive care unit (SICU) after esophagectomy. Methods: We retrospectively reviewed 708 consecutive patients who underwent esophagectomy for primary esophageal cancer during the 4 years before (group A; 322 patients) or 4 years after (group B; 386 patients) the institution of an FTEP. Postoperative morbidity and mortality, LOS, and hospital charges were reviewed. Results: : Compared with group A, group B had significantly shorter median LOS (12 days vs 8 days; P < 0.001); lower mean numbers of SICU days (4.5 days vs 1.2 days; P < 0.001) and telemetry days (12.7 days vs 9.7 days; P < 0.001); and lower rates of atrial arrhythmia (27% vs 19%; P = 0.013) and pulmonary complications (27% vs 20%; P = 0.016). Multivariable analysis revealed FTEP to be associated with shorter LOS ( P < 0.001) even after adjustment for predictors like tumor histology and location. FTEP was also associated with a lower rate of pulmonary complications (odds ratio = 0.655; 95% confidence interval = 0.456, 0.942; P = 0.022). In addition, the median hospital charges associated with primary admission and readmission within 90 days for group B ($65, 649) were lower than that for group A ($79, 117; P < 0.001). Conclusions: These findings suggest that an FTEP reduces patients' LOS, perioperative morbidity, and hospital charges. Abstract : Fast-track esophagectomy protocol (FTEP) involved transferring patients to the telemetry unit instead of the surgical intensive care unit after esophagectomy. FTEP resulted in decreased length of hospital stay, less postoperative complication, and reduced hospital charges compared to traditional care protocol.